Assessing Buildings Hourly Energy Needs for Urban Energy Planning in Southern European Context. (2016) - Ferrari, Simone; Zagarella, Federica
Abstract: For decreasing the fossil fuels consumption and reducing air pollution at urban level, current policies encourage a transition to distributed energy generation (DG) and support initiatives towards district heating and cooling networks (DES - district energy systems), promoting the integration of renewable energy sources (RES). Based on these approaches, the assessment of the energy demand fluctuations of the building stock is preliminary for energy planning at district scale, since systems' operation requires a complex balancing for maximizing the efficiency or minimizing the cost, combining the intermittent nature of RES (except biomasses) with non-RES and/or storage technology. Surveyed literature concerning recent studies aimed at optimizing district energy scenarios revealed that most of the assessment are limited to the seasonal and/or annual based buildings energy needs, while the ones that deal with a proper time scale (i.e. hourly based) refer to specific case studies, which are hardly replicable in other urban contexts. The purpose of the study presented in this paper was to provide reliable reference profiles of buildings thermal energy needs (for both space heating and cooling) with reference to the Italian context. Therefore, a set of building models, representative of typical solutions of different historical periods, was defined for both residential and diffuse tertiary (offices) use. Once elaborated accurate hourly internal loads curves, it was possible to provide, performing detailed simulations with TRNSYS model, profiles of energy need density, referred to cubic meter of building volume, for typical buildings placed in different climatic locations, covering the wide range of Italian context. Based on both the building typologies and the climatic variability considered, assumptions adopted for the study could be extended to other comparable context in southern Europe.